A serious pulmonary infection secondary to disseminated Strongyloidiasis in a patient with Nephrotic syndrome - Ma, Mingming; Cui, Shuang; Luo, Ting; Chen, Zhanhua; Dong, Xiangnan; Huang, Sibo; Yin, Lianghong (Journal of Clinical Nephrology, 2019)
We report a case involving infection with Strongyloides stercoralis found in the sputum of a 66-year-old male patient who had a medical history of nephrotic syndrome and was treated with methylprednisolone and monthly intravenous cyclophosphamide therapy 3 months previously. This patient presented with stubborn pulmonary symptoms and signs, which was the mechanical destruction caused by larval migration. We found strongyloides in his sputum that provided diagnostic proof.